American artists : an illustrated survey of leading contemporary americans - Krantz, Les (Chicago New York : Facts on File Publications New York The Krantz Company Publishers Inc. Chicago, 1985)
Abbett, Robert Kennedy ; Abeles, Kim ; Abrams, Ruth Davidson ; Acconci, Vito ; Adams, Bobbi ; Adickes, David Pryor ; Africano, Nicholas ; Alberga, Alta W. ; Albuquerque, Lita ; Alcorn, John ; Alden, Richard ; Alexander, John ; Alexander, Peter ; Allen, Roberta ; Allison, Dan ; Allman, Margo ; Almy, Max ; Amft, Robert ; Anderson, Laurie ; Anderson, Robert ; Anderson, Ruth ; Anderson, William T. ; Andre, Carl ; de Andrea, John ; Andris, Ruth Ingeborg ; Antonakos, Stephen ; Antreasian, Garo Zareh ; Appel, Karel ; Arakawa, Shusaku ; Arman ; Arneson, Robert ; Arnest, Bernard ; Arnoldi, Charles ; Artschwager, Richard ; Ascher, Mary ; Ashbaugh, Dennis John ; Asher, Lila Oliver ; Asmar, Alice ; Atlee, Emilie Des ; Aubin, Barbara ; Avakian, John ; Avedon, Richard ; Avlon, Helen Daphnis ; Axton, John ; Aycock, Alice ; Aylon, Helène ; Azaceta, Luis Cruz ; Baber, Alice ; Bachinsky, Vladimir ; Bacigalupa, Andrea ; Baeder, John ; Bailey, William ; Balciar, Gerald George ; Baldessari, John ; Ball, Walter ; Bama, James E. ; Bannard, Walter Darby ; Barazani, Morris ; Barker, Al C. ; Barnet, Will ; Barr-Sharrar, Beryl ; Barsano, Ron ; Barta, Dorothy Elaine ; Barth, Frances ; Bartlett, Jennifer ; Bartnick, Harry ; Baskin, Leonard ; Basquiat, Jean-Michel ; Baum, Don ; Baumbach, Harold ; Bavinger, Eugene Allen ; Beal, Jack ; Bear, Marcelle L. ; Bearden, Romare ; Bechtle, Robert ; Behnke, Leigh ; Bell, Charles ; Bell, Larry ; Bell, Lilian A. ; Ben-Zion ; Benglis, Lynda ; Bengston, Billy Al ; Benjamin, Gershon ; Benjamin, Karl ; Bennett, Tim ; Bergstrom, Edith Harrod ; Berguson, Robert Jenkins ; Berman, Ariane R. ; Berman, Fred J. ; Berns, Pamela Kari ; Berry, Carolyn ; Berthot, Jake ; Bertoni, Dante H. ; Bertoni, Mae H. ; Biberman, Edward ; Billian, Cathey R. ; Bisgyer, Barbara G. ; etc.
Engels
boek
Keywords: U.S.A.; Verenigde Staten